Answer:
-45.
Step-by-step explanation:
I am assuming you mean
√25 - 2(3 +4(-2))^2
= 5 - 2(3-8)^2
= 5 - 2 * (-5)^2
= 5 - 2*25
= -45.
b. how old is Brandon
c. what was the difference in their ages 5 years ago?
d. what is the sum of their ages now?
e. what will the sum of their ages be two years from now?
f. what will the difference of their ages be two years from now
will mark the brainliest.
Answer: See explanation
Step-by-step explanation:
a. how old is Cheryl?
Cheryl's age = d + 5
b. how old is Brandon?
d + 5 + 2
= d + 7
c. what was the difference in their ages 5 years ago?
Cheryl age five years ago = d
Brandon's age five years ago = d + 2
Difference = d + 2 - d = 2 years
d. what is the sum of their ages now?
Cheryl's age = d + 5
Brandon age = d + 7
Sum = d + 5 + d + 7
= 2d + 12
e. what will the sum of their ages be two years from now?
Two years from now,
Cheryl's age = d + 5 + 2 = d + 7
Brandon age = d + 7 + 2 = d + 9
Sum = d + 7 + d + 9
= 2d + 16
f. what will the difference of their ages be two years from now
Two years from now,
Cheryl's age = d + 5 + 2 = d + 7
Brandon age = d + 7 + 2 = d + 9
Difference = Brandon age - Cheryl age
= (d + 9) - (d + 7)
= 2 years.
44 cm
154 cm
616 cm
Answer: 154 cm is the answer
Step-by-step explanation:
Answer:
154 cm
Step-by-step explanation:
Answer:
A
Step-by-step explanation:
hope this help
The zeroth derivative of a function is simply the function itself, so the zeroth order linear ODE takes the general form
whose solution is .